Kebebasan Pers Dilihat dari Perspektif Konflik, antara Kebebasan dan Tertib Sosial - Lesmana, Tjipta (Jurnal Ilmu Komunikasi, 2005)
Abstract: Press in this country is joying optimal freedom since the falldown of Soeharto regime. But western-style freedom of the press is echoing numerous negative impacts. Prominent among those impacts are reports or news that considered defamation. Several libel cases have been brought to the court. Defendants (publishers or chiefeditors) are frequently lost the cases, being nished by imprisonment and/or huge emount of fine, resulting in the outcry of some journalists. The judges are accused of obstructing press freedom, or no apprehension whatsoever on the vital role of the press in democracy.